EDUSECURE: EDUCATIONAL APP FOR CYBER SECURITY - NUR BAQIYAH, HAIDIR (Universiti Malaysia Sarawak (UNIMAS), 2023)
In today’s digital age, almost everyone especially college students rely on technology and the Internet. As a result, the unexpectedly rapid growth of cyber users creates the need for healthy cyber habits and awareness. This is due to the increasing number of cyber security incidents recorded. The increase in cyber security incidents shows that cyber security awareness may still be insufficient among cyber users. Some cyber security incidents occurred because of social engineering, poor password practices, and malicious mobile applications. Therefore, from these incidents and the data collected through the questionnaire, an educational app called EduSecure is proposed to assist in cyber security education and awareness among UNIMAS students. As the proposed system is a mobile application, it can be the easiest and the best way to reach cyber users. EduSecure, the educational app for cyber security will provide learning topics regarding password practices, social engineering, and mobile applications. Quiz games are also included for the user to test their understanding after completing the learning topics. EduSecure focuses on promoting gamification practices and implementing threat escape room concept in cyber security. The use of the threat escape room in cyber security increases motivation and promotes cyber security awareness learning. Therefore, the threat escape room has greater potential than a traditional learning methodology about cyber security. The usability testing reveals that EduSecure demonstrates good usability and effectively enhancing users’ understanding of cyber security. The app empowers users by providing valuable insights that contribute to their improved knowledge of cyber security. Furthermore, the findings of this work also demonstrated the effectiveness of employing gamification techniques and threat escape rooms as a cyber security learning tool